2010
DOI: 10.1007/s10654-010-9431-y
|View full text |Cite
|
Sign up to set email alerts
|

A successful implementation of e-epidemiology: the Danish pregnancy planning study ‘Snart-Gravid’

Abstract: The attraction of being able to use the internet for the recruitment of an epidemiologic cohort stems mainly from cost efficiency and convenience. The pregnancy planning study ('Snart-Gravid')-a prospective cohort study of Danish women planning a pregnancy-was conducted to evaluate the feasibility and cost efficiency of using internet-based recruitment and follow-up. Feasibility was assessed by examining patient accrual data over time, questionnaire-specific response rates and losses to follow-up. The relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 23 publications
(26 reference statements)
2
72
0
Order By: Relevance
“…2 Important features of such non-probabilitybased research include widespread advertising of the study's website without any control over the number of individuals reached or the types of individuals recruited, 2 as well as improved efficiency with longer follow-up and larger samples. 5 Given that target population coverage and access barriers are rapidly diminishing, 4 authors have indicated that any challenges associated with e-cohorts are likely transitional, 29 and will be solved in the near future. 8 Original aspects regarding the NutriNet-Santé design and methodology include its very large sample size drawn from the general population, a broad focus on nutrition, an assessment of a wide range of personal characteristics and recurrence of the multimedia recruitment campaigns, with each new effort drawing attention to specific public health recommendations regarding diet and nutrition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Important features of such non-probabilitybased research include widespread advertising of the study's website without any control over the number of individuals reached or the types of individuals recruited, 2 as well as improved efficiency with longer follow-up and larger samples. 5 Given that target population coverage and access barriers are rapidly diminishing, 4 authors have indicated that any challenges associated with e-cohorts are likely transitional, 29 and will be solved in the near future. 8 Original aspects regarding the NutriNet-Santé design and methodology include its very large sample size drawn from the general population, a broad focus on nutrition, an assessment of a wide range of personal characteristics and recurrence of the multimedia recruitment campaigns, with each new effort drawing attention to specific public health recommendations regarding diet and nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Its capacity to handle high activity volumes, cost-effectiveness, interactive interface with built-in controls, the relatively quick finetuning of instruments, the streamlined data management, access and follow-up, and reduced social anxiety/desirability have given the Internet the high ground in research endeavours. 3 4 8 9 Moreover, the Internet-using population nowadays includes the large majority of individuals and households, 10 and continues to expand across social strata.…”
Section: Introductionmentioning
confidence: 99%
“…SF is an expansion of the Snart Gravid ("Soon Pregnant") study, which has been described previously (15,16). Recruitment for SF was Internet-based and began in 2011 with advertisements placed on Danish health-related websites and blogs.…”
Section: Study Populationmentioning
confidence: 99%
“…In some countries (Australia, Canada, France, Russia, the Netherlands, and the USA), the study sample was small compared to the general birthing population, 6 and thus, the generalizability of our findings for these specific countries should be interpreted with caution. Using this kind of an approach, a conventional response rate cannot be calculated, but reasonable validity can be expected based on previous epidemiological studies using web-based recruitment methods [12][13][14] and based on our comparison with the birth population in the participating countries. 6 Overall, the age structure of the study population matches the birthing populations in each country quite well.…”
Section: Discussionmentioning
confidence: 74%